Paróquia: casa da iniciação e comunidade de sujeitos eclesiais - Reinert, João Fernandes (Revista Eclesiástica Brasileira, 2019)
O presente artigo pretende aproximar três temas eclesiológico-pastorais, frutos das reflexões das Assembleias dos bispos do Brasil: paróquia comunidade de comunidades, sujeitos eclesiais, e iniciação à vida cristã. Não se trata de uma análise de tais documentos, mas sim, de uma reflexão ampliada sobre cada um dos três temas, no intuito de captar o que se pretende de cada uma das realidades indicadas e, sobretudo, de perceber o que há de comum entre elas. Relacionalidade e comunhão são o DNA e o fio condutor da nova paróquia, chamada “comunidade de comunidades”, composta de “sujeitos eclesiais” e casa de “iniciação à vida cristã de inspiração catecumenal”. Abstract: The present article intends to bring together three ecclesiological-pastoral themes, fruit of the reflections in the Assemblies of Brazilian bishops: the Parish as a community of communities, ecclesial subjects and initiation to the Christian life. We are not dealing with an analysis of such documents, but rather with a deeper reflection about each of the three themes, hoping to capture what is the intention behind each of the realities indicated and, above all, what they have in common. Relationality and communion are the DNA and the driving force behind the new Parish, called “community of the communities” made up of “ecclesial subjects” and the home for the “initiation to the Christian life of catechumenal inspiration”. Keywords: Parish; Community of communities; Ecclesial subject; Initiation to the Christian life; Relationship; Communion.